Teacher change through professional development: an embedded case study of Vietnamese tertiary EFL teachers adopting blended learning - Kieu, Huyen Tram (2025)
This thesis presents a PhD project conducted in the context of blended learning (BL), which is emerging as a significant educational reform globally and in Vietnam. It investigates the adoption of BL by English as a Foreign Language (EFL) teachers at a Vietnamese university, focusing on teacher change resulting from a tailored professional development (PD) program.